Three new species of the louse genus Saemundssonia (Insecta: Phthiraptera: Philopteridae) - Palma, Ricardo L. (Zootaxa, 2012)
I describe and illustrate three new species of chewing lice in the genus Saemundssonia, collected from seabirds in NewZealand, the Galápagos and other islands of the Pacific Ocean. They are: Saemundssonia (Saemundssonia) albatrossa n.sp. from Phoebetria palpebrata, Thalassarche chrysostoma, and Thalassarche impavida; Saemundssonia(Saemundssonia) creagrusa n. sp. from Creagrus furcatus; and Saemundssonia (Saemundssonia) gygisa n. sp. from Gygis alba candida.